Diseminasi teknologi alat tabur pupuk sederhana bagi petani di Kecamatan Buntu Batu Kabupaten Enrekang - Suherman; Patahuddin; Syawal; Nasrullah A; Nurhapsa; Iradhatullah Rahim; Sukmawati; Rahmat Fardi Asli; Edy Ardyansyah (Jurnal Dedikasi Masyarakat, 2023)
Agricultural productivity cannot be separated from the use of technology by farmers. For example, in Enrekang Regency, there are still farmers who have not maximized the use of technology because it is considered expensive. Technology can be engineered but does not change the work function as an appropriate technology that is easy and cheap. For example, for corn farmers, fertilization is still traditional and takes up much time and energy, making farmers tired. Therefore dissemination was carried out to accelerate technology adoption, one tool that is easy to make using simple and inexpensive materials is a fertilizer sowing tool that is used to fertilize crops such as corn, chili, tomatoes, mustard greens, or cabbage for farmers in Buntu Batu District, Kabupaten Enrekang. Activities carried out by counseling and training methods as well as demonstrations of the use of tools. This fertilizer-sowing tool is made of several sizes of pipes that work on the same principle as a drill and the fertilizer that comes out can be adjusted to the needs of the plants. Participants appreciated the results of the socialization activities in the form of counseling and training on assembling fertilizer sowing tools from PVC pipes and demonstrations. The people in Pasui Village and Lunjen Village responded well to the socialization of the sow fertilizer tool because the technology offered was very much needed and helped farming communities who complained of back pain after every fertilization. Local farmers will then reproduce the existence of these tools after learning how to make them so that they can enjoy them directly.